A methylene blue-based near-infrared fluorescent probe for rapid detection of hypochlorite in tap water and living cells. Issue 26 (18th April 2018) - Huang, Xin; Li, Zhipeng; Cao, Tingting; Cai, Qian; Zeng, Chengchu; Fu, Hua; Hu, Liming
Abstract : We developed aMB -based probe to detect OCl −, whose product is almost non-toxic. The fluorescence enhancement times are large. Abstract : A methylene blue-based near-infrared fluorescent probe was designed for the selective determination of hypochlorite (ClO − ), over other reactive oxygen species or interfering agents. Acetylated methylene blue was synthesized by introducing the acetyl group into the methylene blue framework, which can specifically recognize exogenous and endogenous ClO − . The acetylated methylene blue fluorescent probe was characterized by 1 H NMR, 13 C NMR and HRMS. The response process and possible mechanism were studied using products of the probe. The emission response of the probe to ClO − presented good linear relationship in the 0–60 μM concentration range, with the detection limit of 0.1 μM (measured at 660 nm and 690 nm). The absorption and emission wavelengths of acetylated methylene blue are both in the near-infrared region; in addition, the probe itself and the degradation products were well-dissolved in water and have almost no toxicity. The probe was used for intracellular ClO − imaging and showed a large fluorescence enhancement (about 200-fold increase).